2007
DOI: 10.1111/j.1365-2133.2007.08313.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasma D-dimer concentration in patients with systemic sclerosis

Abstract: The association between high levels of plasma D-dimer (>or=500 ng mL(-1)) and macrovascular involvement in patients with SSc is likely to be an innovative issue. We suggest that D-dimer levels may be a helpful additional test to identify patients with SSc at risk to develop thrombotic arterial complications (peripheral arterial disease, stroke and coronary event); such patients with high levels of plasma D-dimer (>or=500 ng mL(-1)) may require close monitoring of vascular parameters, including especially macro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…Additionally, plasmin is known to regulate vascular endothelial functions, and influence the progression of various cardiovascular diseases through fibrinolysis, the degradation of matrix proteins, and the activation of growth factors [ 20 ]. The levels of plasmin-α2AP and D-dimer are elevated in patients with SSc [ 21 , 22 ], and plasmin may also affect vascular dysfunction in SSc. α2AP may cause vascular disorder not only through inhibition of VEGF responses but also through plasmin inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, plasmin is known to regulate vascular endothelial functions, and influence the progression of various cardiovascular diseases through fibrinolysis, the degradation of matrix proteins, and the activation of growth factors [ 20 ]. The levels of plasmin-α2AP and D-dimer are elevated in patients with SSc [ 21 , 22 ], and plasmin may also affect vascular dysfunction in SSc. α2AP may cause vascular disorder not only through inhibition of VEGF responses but also through plasmin inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, integrin αIIb and glycoprotein Ibβ, receptors for von Willebrand factor expressing on platelets, are abnormally up-regulated in SSc [ 39 ]. Given that sensitive markers of fibrinolytic enhancement, such as plasma levels of D-dimer and plasmin-α2-plasmin inhibitor complex (PIC), are elevated in SSc patients [ 51 , 52 , 53 , 54 ], the altered balance of coagulation/fibrinolysis system appears to cause a variable degree of luminal thrombosis following vascular injury, contributing to impaired peripheral circulation, the induction of inflammation and the subsequent activation of vascular cells (endothelial cells and pericytes/vascular smooth muscle cells) and fibroblasts [ 55 , 56 , 57 ].…”
Section: The Common Ssc-specific Pathologic Cascade Across Multiplmentioning
confidence: 99%
“…It is reported that ECs synthesize tPA, uPA, uPAR, and PAI-1, and that fibrinolytic regulators play an important role in the maintenance of endothelial homeostasis [15,16,17,18,19,20]. The levels of plasmin-α2AP complex and D-dimer in plasma are elevated in SSc [21,22,23] and the expression of α2AP is elevated in fibrotic tissue of SSc model mice and dermal fibroblasts obtained from patients with SSc [24,25]. α2AP deficiency attenuates the development of fibrosis in SSc model mice [26,27] and uPAR deficiency promotes the development of fibrosis [28].…”
Section: Introductionmentioning
confidence: 99%